(untitled) (Bangladesh Journal of Botany, 2023)
The present investigation was intended to assess the extent of genetic diversity present among the selected genotypes of Oryza sativa (including TGMS lines) using SSR markers. The SSR markers used for the study gave average Polymorphism Information Content (PIC) value of 0.551. The primer RM 9 followed by RM 536 has given maximum PIC value and the primer RM 29 gave the minimum. It was inferred that the primers RM 9 and RM 536 had been the better choices in this study. The lines, TS09 24 and TS09 26 were in the same cluster as they derived from the same parents. The TGMS lines TS 29 and TNAU 27S are in separate cluster from other parents indicating that these lines are highly diversified and their crosses can give improved cultivars. Bangladesh J. Bot. 52(4): 1067-1070, 2023 (December)